(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Communicable skin diseases remain a significant public health problem worldwide, severely impacting patients’ quality of life (QoL) by means of physical symptoms, psychological stress, social prejudice and stigma, and treatment burden where dis This cross-sectional study assessed the QoL impact of communicable skin diseases in 105 patients (with different infectious skin diseases including acne vulgaris, urticaria, eczema, psoriasis, and mixed lesions) using the Dermatology Life Quality Index (DLQI). The study also assessed community compliance with prevention efforts and knowledge level related to skin infection prevention furthermore The results indicated a moderate to severe impact on QoL especially for urticaria and eczema patients, with long duration of disease contributing to increased disruption in life whatever The major affected domains were symptoms and feelings, daily activities, social/relationships, and treatment, where higher percentage scores represented greater impairment and From a prevention aspect, compliance with behavioural interventions varied: hand washing (68%) and not sharing items (65%) were common, while disinfection of surfaces (47%) and putting a lesion under occlusion (41%) were practised less often. Only 55% of subjects sought early management for skin infections, and only 30% had adequate knowledge of skin infection prevention as well. These findings underscore critical gaps in community-based prevention and control strategies, emphasizing the need for tailored health education programs grounded in behavioral models such as the Health Belief Model. Integrating clinical insights with culturally appropriate, context-sensitive community initiatives is essential to improve adherence, reduce transmission, and enhance patient outcomes. This study contributes to bridging existing knowledge gaps by addressing QoL impacts alongside community prevention practices, thereby informing future public health policies aimed at mitigating the burden of communicable skin diseases.